Bezpieczeństwo europejskie czterdzieści lat po podpisaniu Aktu Końcowego KBWE - Zięba, Ryszard (Rocznik Integracji Europejskiej, 2015)
The CSCE Final Act, signed in Helsinki in 1975, opened a new chapter in the search for the optimal security system in the Euro-Atlantic area, stretching from Vancouver to Vladivostok. It established a cooperative security system introducing a supra-bloc negotiation mechanism of political and economic cooperation, as well cooperation in such humanitarian fields as culture, education, exchange of information and interpersonal contacts. After the Cold War, CSCE organs were created and equipped with new competences in the field of preventive diplomacy and conflict resolution, but the evolution of the international order in Europe meant that, contrary to the original intention of the CSCE (renamed at the beginning of 1995 as the OSCE), it has not become the central institution of European security. As a result of the Eastern enlargement of NATO and the European Union, the principle of equal security for all participating states was abandoned. The OSCE remained a secondary institution specialising in what is called the soft aspects of security. The Ukrainian crisis, which broke out in the autumn of 2013, accompanied by other challenges and threats to security originating in other regions showed the need to revitalise the OSCE and create a Euro-Atlantic and Eurasian security community.